Dampak Belanja Pemerintah Terhadap Konversi Hutan ke Pertanian di Indonesia - Puspitasari, Widyaningsih Ratna (Pusjar SKPP Lembaga Administrasi Negara, 2018)
This study analyzes the impacts of government spending on land use conversion from forest to agriculture based on national budget allocation in Indonesia. As agriculture expansion and the government spending on agriculture increase especially during this more than ten-year period, it is suspected that the conversion of land from forest to agriculture gradually increases. Therefore, the increase of government spending on agriculture may be one of the contributing factors to deforestation. Balanced panel data from 33 provinces in Indonesia that covers a ten-year period between 2006 and 2015 was used to examines the indirect effects of government spending on agriculture, total government spending over GRDP, and public spending on land use conversion. The generalized method of moment estimation (GMM) technique was applied in this research to investigate relationship between government spending and deforestation. The result showed that there is an indirect impact from increasing government spending: there is an increase in the total amount of land use conversion from forest to agriculture in Indonesia. This study depicts that an increase in government spending on agriculture and total government spending over GRDP have a significant positive impact on deforestation. Meanwhile, public spending has no significant effect on deforestation. Keywords: Deforestation, GMM, government spending Abstrak Penelitian ini bertujuan untuk menganalisa dampak belanja pemerintah terhadap deforestasi, berdasarkan anggaran nasional belanja pemerintah di Indonesia. Meningkatnya perluasan lahan pertanian yang diikuti dengan peningkatan belanja pemerintah untuk sektor pertanian dalam kurun waktu lebih dari 10 tahun terakhir ini memungkinkan terjadinya peningkatan konversi lahan. Peningkatan belanja pemerintah yang ditujukan untuk sektor pertanian dapat menjadi salah satu faktor pemicu deforestasi. Menggunakan panel data dari 33 provinsi di Indonesia selama 10 tahun, dari tahun 2006 s.d 2015, penelitian ini mengkaji dampak tidak langsung dari belanja pemerintah di bidang pertanian, total belanja pemerintah per PDRB, dan belanja pemerintah di public sector terhadap deforestasi. Menggunakan system generalized method of moment estimation (GMM), penelitian ini menganalisa hubungan antara belanja pemerntah dan deforestasi. Hasil empirik menunjukkan bahwa terdapat dampak tidak langsung dari peningkatan belanja pemerintah: adanya peningkatan konversi lahan dari hutan untuk pertanian. Penelitian ini juga menunjukkan bahwa peningkatan belanja pemerintah di bidang pertanian dan total belanja pemerintah per PDRB memiliki dampak siknifikan terhadap deforestasi. Sedangkan belanja pemerintah untuk sector public tidak memiliki dampak untuk meningkatkan deforestasi. Kata kunci : Deforestasi, GMM, belanja pemerintah